Pembangunan Aplikasi Mycar Siswa UTHM - Mat Saad, Alfi Rahmi; Rabatul Aduni Sulaiman (Applied Information Technology And Computer Science, 2021)
Nowdays, E-hailing services among university students are in high demand. This situation has resulted in some university students in UTHM are offering offline e-hailing services without being registered with any recognized company. This scenario has caused some people and users anxiety. The issue that has been raised in this regard is the issue of user safety when using this offline e-hailing service. In light of the weaknesses of the existing system, an application system was proposed to be developed to control all processes involving e-hailing services among UTHM students. The system to be developed is Android-based application which is MyCar Siswa UTHM Application System as a proper platform to running the service and also web-based application for collecting user, driver and travel records that will be monitored by UTHM security organization. The methodology used in the development of this application is a prototype model. This developed application will use flutter framework and Firebase as a database. The application will provide a platform that makes it easy for students to find and place e-hailing service. The application will automatically detect the current position of the passenger when ordering using GPS technology. In addition, the app also has a rating score module for services that have been offered by drivers. Hoppefully the application can solve the previous problem and also create a more systematic application system for the e-hailing service among the UTHM students.